Understanding climate change adaptation governance and building resilience among local communities in Senegal A Review - Arimiyaw, Abdul Wahid; Osei-Amponsah, Charity; Amarnath, Giriraj (CGIAR System Organization, 2022)
In this literature review, we examine climate change adaptation governance and resilience building among communities in Senegal. We examine existing policies, governance structures, and decision-making processes in climate change adaptation issues at different governance levels for food related sectors (agriculture, natural resource, including forestry, water and energy). Second, we identify key programmes/projects, knowledge gaps, social inclusion and equity gaps in climate change adaptation issues at different governance levels for food related sectors. Third, we unravel the challenges and opportunities in climate change adaptation issues at different governance levels for food related sectors. Lastly, we identify bottom-up approaches on climate adaptation and system transformation processes in Senegal.